Boosting electrosynthesis of ammonia on surface-engineered MXene Ti3C2. (June 2020) - Xia, Jiexiang; Yang, Shi-Ze; Wang, Bin; Wu, Peiwen; Popovs, Ilja; Li, Huaming; Irle, Stephan; Dai, Sheng; Zhu, Huiyuan
Abstract: Seeking a breakthrough in the development of efficient nitrogen fixation catalysts has become the frontier of energy and chemical conversion schemes. Here, we report that the MXene Ti3 C2 can serve as a promising catalyst for the electrochemical N2 reduction reaction (NRR) under ambient conditions. The electrocatalytic performance of Ti3 C2 can be further optimized through surface engineering. Specifically, Ti3 C2 with the increased surface hydroxyl moieties demonstrates enhanced production of NH3 with a yield rate of 1.71 μg h −1 cm −2, a Faradaic efficiency of 7.01% at −0.2 V vs. RHE at 20 °C and an even higher yield rate of 12.46 μg h −1 cm −2 together with a Faradaic efficiency of 9.03% at −0.2 V vs. RHE at 60 °C. The detailed electrochemical analysis suggests that the surface hydroxyl modification can effectively facilitate the electron transfer, surface adsorption and activation of dinitrogen. Our work sheds light on the development of efficient NRR catalysts based on earth-abundant elements. Graphical abstract: Image 1 Highlights: MXene Ti3 C2 is active for the electrochemical N2 reduction reaction under ambient conditions. Surface engineering of MXene Ti3 C2 is highly effective in boosting the electrochemical performance. Surface hydroxyl modification facilitates the electron transfer and the adsorption and activation of dinitrogen.